Review: Targeted therapy in renal cancer - Tanya B. Dorff; Amir Goldkorn; David I. Quinn (Therapeutic Advances in Medical Oncology, 2009)
Renal cell cancer (RCC) has an increasing incidence internationally and is a disease for which there have been limited therapeutic options until recently. The last decade has seen a vastly improved understanding of the biological and clinical factors that predict the outcome of this disease. We now understand some of the different molecular underpinnings of renal clear cell carcinoma by mutation or silencing of the von Hippel Lindau (VHL) gene and subsequent deregulated proliferation and angiogenesis. Survival in advanced disease is predicted by factors (performance status, anemia, hypercalcemia, and serum lactate dehydrogenase, time from diagnosis to recurrence) incorporated into the Memorial Sloan Kettering Cancer Center (MSKCC) criteria (also referred to as ‘Motzer’ criteria). These criteria allow classification of patients with RCC into good, intermediate and poor risk categories with median overall survivals of 22 months, 12 months and 5.4 months, respectively. Predicated upon these advances, six new targeted drugs (sorafenib, sunitinib, temsirolimus, everolimus, bevacizumab and pazopanib) have been tested in well-designed phase III trials, selected or stratified for MSKCC risk criteria, with positive results. All of these new drugs act at least in part through vascular endothelial growth factor (VEGF) mediated pathways with other potential therapeutic impact on platelet-derived growth factor (PDGF), raf kinase and mammalian target of rapamycin (mTOR) pathways. Importantly, data from each of these trials show a consistent doubling of progression-free survival (PFS) over prior standard of care treatments. In addition, sorafenib, sunitinib and temsirolimus, have demonstrated significant overall survival (OS) benefits as well; further follow-up is required to determine whether the disease control exhibited by everolimus and pazopanib will translate into a survival advantage. These drugs are generally well tolerated, as demonstrated by quality-of-life improvement in clinical trials, and result in clinical benefit for in excess of 70% of patients treated. They have challenged the traditional outcomes of clinical trial design by achieving their benefits with relatively few radiographic responses, but high rates of disease stability. The unique side-effect profile coupled with the chronicity of therapy requires increased vigilance to maximize exposure to the drugs while maintaining quality of life and minimizing toxicity. This review focuses on the background, clinical development and practical use of these new drugs in RCC.